Initial results in Prony analysis of power system response signals - Scharf, Louis L., author; Demeure, Cédric, author; Hauer, John F., author; IEEE, publisher (Colorado State University. Libraries, 1990)
Prony analysis is an emerging methodology that extends Fourier analysis by directly estimating the frequency, damping, strength, and relative phase of modal components present in a given signal. The ability to extract such information from transient stability program simulations and from large-scale system tests or disturbances would be quite valuable to power system engineers. This paper reports early results in the application of this method to stability program output. It also includes benchmarks against known models and a brief mathematical summary.
Keywords: singular value; signal analysis; dynamics; stability; eigenvalue; Prony; modal analysis